Pengaruh Gadget terhadap Perilakuanak Kelas Vi SD IT Al-Maqom - Putri Auliya; Suci Padilah Sukmawati; Sri Mulyeni (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
The purpose of this study is to find out how the behaviour of students in class VI of SD IT Al-Maqom in relation to the use of gadgets. Along with the rapid development of technology, the use of gadgets is now an important part of everyday life, including for students. This study used a quantitative approach with a direct regression method, involving 70 learners as samples. Data was obtained through the distribution of questionnaires that measured the influence of gadget use on learner behaviour. The results of the analysis show that the use of gadgets has a significant influence on learners' behaviour with an influence level of 76.3%. Although the impact of gadgets is considerable, this study also acknowledges the existence of other factors, such as environment, parenting style, and genetic factors, which also influence learners' behaviour, although these factors were not examined in depth in this study. In addition, habits, social interaction patterns, and the role of parents and teachers can also influence learners' gadget use. In conclusion, gadget use has a significant influence on learners' behaviour in class VI of Al-Maqom IT Elementary School.